2007
DOI: 10.1590/s0034-89102007000800012
|View full text |Cite
|
Sign up to set email alerts
|

Resposta brasileira ao controle da tuberculose

Abstract: Tuberculosis remains a public health problem in Brazil. In 2003, controlling tuberculosis was highlighted as a priority among health public policies. The article reports the Brazilian response to this challenge, describing the main strategies of the National Control Plan for 2003 to 2006. Among its main results are: expansion of strategic coverage of the supervised treatment, increase in the percentage of cure, decrease in the number of patients' treatment dropout, and of the incidence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
19

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 1 publication
1
22
0
19
Order By: Relevance
“…In Brazil, the disease is associated with vulnerable populations, poverty and agglomerated urban areas with high population density 2 . The municipality of São Paulo, a priority for the control of TB 3 , is a large metropolis permeated by social inequalities, where an important part of the population is inserted in the urban space in a precarious way and difficult access to public goods 4 . Considering the relevance of TB in the MSP, and that the disease acts as an indicator of public health and the efficiency of health services 5 , the objective of this study was to describe the epidemiological profile of all new TB cases reported between 2006 and 2013.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, the disease is associated with vulnerable populations, poverty and agglomerated urban areas with high population density 2 . The municipality of São Paulo, a priority for the control of TB 3 , is a large metropolis permeated by social inequalities, where an important part of the population is inserted in the urban space in a precarious way and difficult access to public goods 4 . Considering the relevance of TB in the MSP, and that the disease acts as an indicator of public health and the efficiency of health services 5 , the objective of this study was to describe the epidemiological profile of all new TB cases reported between 2006 and 2013.…”
Section: Introductionmentioning
confidence: 99%
“…A endemia segue como grande problema da saúde pública pela sua capacidade de atingir com maior intensidade as populações marginalizadas, 4 sendo considerada um marcador social impor tante em relação às precárias condições de sobrevivência dos indivíduos da maioria das grandes cidades do País. Em geral, estas capitais apresentam CI mais elevados, devido à alta densidade demográfica, aliada às situações de exclusão social, o que pode elevar o risco de infecção.…”
Section: Reflection -Reflexiónunclassified
“…A busca ativa de sintomáticos respiratórios deve ser uma atitude permanente e incorporada à rotina de atividades de todos os membros da equipe de saúde, 4 …”
unclassified
“…According to the World Health Organization (WHO), in 2008 and according to the number of cases, Brazil was among the 22 countries responsible for 80% of all tuberculosis cases in the world 1 . With regard to mortality, the estimated occurrence was approximately 8,400 deaths attributed to tuberculosis, which is equivalent to a rate of 1.3 deaths per 100,000 inhabitants [1][2][3][4][5][6] . Since 2003, tuberculosis control has been prioritized among public health policies [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they can result in the development of bacterial resistance and its spread [13][14][15][16] . In 2005, the Brazilian government made a pact with the WHO, aiming to cure 85% of all estimated tuberculosis cases and maintaining the number of treatment drop-out cases worldwide below 5% [2][3][4][5][6][7][8] . The .…”
Section: Introductionmentioning
confidence: 99%